PENGARUH AUGMENTED REALITY TERHADAP PEMAHAMAN KONSEP BARISAN PADA MAHASISWA - Lubis, Ariyanto; Purba, Diva Novita Angely Putri; Simangunsong, Erika; Simanullang, Michael Christian (LPPM Universitas Bina Bangsa, 2025)
Technological advances in education have brought significant changes in learning methods, including the use of Augmented Reality (AR) as an interactive media to improve students' understanding of the concept of rows. This study aims to analyze the effect of using AR on the understanding of the concept of sequence in the Real Analysis course, especially in the aspects of sequence limit, sequence tail, and sequence operation. The approach used in this research is qualitative with descriptive analysis method, where the data is collected through tests given to three students who are the research subjects. Augmented reality developed in this study visualizes the concept of limit of a line by displaying points that are getting closer to the x-axis, as well as adding elements of the tail of the line to test students' understanding of the part of a line. The results showed variations in students' level of understanding of each concept tested, and revealed some conceptual errors that occurred during the testing process. The discussion in this study highlights the effectiveness of AR in facilitating student understanding, as well as identifying factors that influence success in understanding the concept of rows in more depth.